Pengaruh Content Marketing, Influencer Dan Online Customer Review Terhadap Keputusan Pembelian Pada Pengguna Media Sosial Tiktok (Studi Kasus Pada Mahasiswa FEB Universitas Islam Malang Angkatan 2019) - Anggita Valentina; Mohammad Rizal; Ratna Tri Hardaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to analyze and describe the effect of content marketing, influencers and online customer reviews on purchasing decisions on social media users on TikTok (a case study of unisma feb students class of 2019. The population in this study were S1 students of the Faculty of Economics and Business, Islamic University of Malang, class of 2019, both from the Management study program as many as 598 students, Accounting as many as 213 students, and Islamic Banking as many as 93 students with a total of 904 people.Then from this number a sample was taken of 90 people using the malhotra formula.The variables used in this research are decision variables purchase (the dependent variable), while the independent variables are content marketing, influencer and online customer review.The results of this study concluded that there was a positive and significant influence between content marketing, influencer and online customer review variables on purchasing decisions and simultaneously concluded that there was an influence between content marketing, influencer and online customer review variables on purchasing decisions. Keywords: purchase decision, content marketing, influencer and online customer review.